Nível de funcionalidade e de atividade física em pacientes com amputação transfemoral - Pacheco, Caroline da Silva; Hansen, Renata Michelon (My University, 2023)
Objective: Evaluate the level of functionality and physical activity in patients with transfemoral amputation, seeking to answer whether the level of physical activity and age interfere with the functionality of patients. Methods: This is an observational, analytical and cross-sectional study, with a sample of 17 participants, adults and elderly, of both sexes, with transfemoral amputation in the preprosthesis phase and who had a registration at the Clinical Center of the University of Caxias do Sul (CECLIN ). The following instruments were used: Questionnaire for sample identification, Amputee Mobility Predictor (AMP), Functional Independence Measure (MIF), Timed Up And Go (TUG) and the International Physical Activity Questionnaire (IPAQ). Descriptive statistics, Kruscall Wallis test and Spearman correlation (p<0.05) were used. Results: Very active (23.5%) and active (52.9%) patients proved to be more functional and independent than sedentary ones through the AMP and FIM tests (p=0.01 and p=0.05). When correlating functionality with age, younger patients demonstrated significantly greater functionality in AMP (p=0.01) and TUG (p=0.05). Age did not significantly interfere with the level of physical activity (p= 0.34). Conclusion: This study found that individuals with a higher level of physical activity demonstrated to be more functional and independent than the more sedentary ones and that younger patients demonstrated greater functionality than the older ones. [resumo fornecido pelos autores]
Avaliar o nível de funcionalidade e atividade física em pacientes com amputação transfemoral, buscando responder se o nível de atividade física e a idade interferem na funcionalidade dos pacientes. Métodos: Trata-se de um estudo observacional, analítico e transversal, com amostra de 17 participantes, adultos e idosos, de ambos os sexos, com amputação transfemoral na fase de pré-protetização e que possuíam cadastro no Centro Clínico da Universidade de Caxias do Sul (CECLIN). Foram utilizados os seguintes instrumentos: Questionário para identificação da amostra, Amputee Mobility Predictor (AMP), Medida de Independência Funcional (MIF), Timed Up And Go (TUG) e o Questionário Internacional de Atividade Física (IPAQ). Foi utilizada estatística descritiva, teste Kruscall Wallis e Correlação de Spearman (p<0,05). Resultados: Pacientes muito ativos (23,5%) e ativos (52,9%) demonstraram ser mais funcionais e independentes que os sedentários através dos testes AMP e MIF (p=0,01 e p=0,05). Ao correlacionar a funcionalidade com a idade, os pacientes mais jovens demonstraram, significativamente, maior funcionalidade na AMP (p=0,01) e no TUG (p=0,05). A idade não interferiu de forma significativa no nível de atividade física (p= 0,34). Conclusão: Este estudo constatou que indivíduos com maior nível de atividade física demonstraram ser mais funcionais e independentes que os mais sedentários e que pacientes mais jovens demonstraram maior funcionalidade do que os mais velhos. [resumo fornecido pelos autores]
Keywords: Fisioterapia; Análise da marcha; Amputações; Extremidade inferior; Qualidade de vida